The Effect Of Dumbell Exercise Using Resistance Bands On Arm Muscle Strength In The Petanque Team Of Universitas Muhammadiyah Palopo - Sahariana Sahariana; A. Heri Riswanto; Ahmad Ahmad; Rachmat Hidayat (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effect of dumbbell exercises using resistance bands on arm muscle strength in the petanque team at the University of Muhammadiyah Palopo. The method used in this research is a one-group pretest-posttest experimental design with a quantitative approach. From the results of a study that has been carried out on the effect of dumbell training using resistance bands on arm muscle strength in the Petanque Team at the University of Muhammadiyah Palopo. Moreover, the results of data processing with statistical analysis show that this research has a sig value of 0.000 <0.05, which means that Ho is rejected. Thus, dumbell training using resistance bands significantly affects arm muscle strength in the Petanque Team at the University of Muhammadiyah Palopo.